A Review on the Use of Google Classroom in the learning of English - Intan Syahidah, Zulkafa; Zuraina, Ali (2020)
The invention of the internet has changed the teaching and learning processes. Blended learning comes into the light as both teachers and learners become more active. The traditional classroom setting is now injected with an online course to cater their needs. In parallel to that, a lot of applications are created in order to aid the teaching and learning development including Moodle, Edmodo and Google Classroom. With the outbreak of Covid-19 pandemic, one of the most used education applications is Google Classroom (GC). Its flexibility allows learners to provide immediate response and access materials that cannot be achieved via traditional classroom learning before this. GC is deemed to hold several advantages over other forms of applications. Therefore, majority of university and school students adapt quickly to GC. Some researches claimed that GC could provide outputs that are more relevant and needed for the students. However, studies on the effects on the use of GC as a medium of learning English language are still scarce. Hence, this review is conducted to investigate the students’ perception and challenges of Google Classroom in English language teaching and learning. These implications display potential use of GC for collaboration in term of the learners’ acceptance, motivation and performance. It is hoped that GC can be utilized as one of the teaching media in enhancing the mastery of English language better, if not faster.